Toward Intervocality: Linklater, the Body, and Contemporary Feminist Theory. Issue 2 (4th May 2019) - Cahill, Ann J.; Hamel, Christine
ABSTRACT: This article inaugurates a conversation between the fields of voice training and contemporary feminist theories of the body. The article begins with a consideration of the development of Kristin Linklater's highly influential work Freeing the Natural Voice, and the significant advancements it represented in the field of voice. The article proceeds to a description of the field of contemporary feminist theories of the body, highlighting those insights and developments that either resonate most clearly with Linklater's work or represent promising avenues for the next evolution of voice training. Those theories not only share Linklater's rejection of Western dualism but also cast doubt on any references to the natural (i.e. pre-political) body, including references to the natural voice. The article then argues that such evolution should take up more directly the relationality of the voice (what the article terms "intervocality"), an understanding of the body as ineluctably embedded within social and political dynamics, and a recognition of the profound influence of structural inequality on both vocality in general and vocal training in particular. The article concludes by gesturing toward a model of vocal generosity that may provide a framework for that next evolution.